Gamification as a strategy to enhance vocabulary in the students of first basic grade at unidad educative Salinas Innova. Salinas, province of Santa Elena. School year 2016-2017. - Valdivieso Haz, Diana Carolina (2016)
Gamification is defined as using the mechanics of games to make learning more engaging. The present research paper has as objective to enhance vocabulary through gamification as a strategy. The components of the gamification definitely increase the motivation and commitment of students during class development using free easy software programming through recreational activities that stimulate memory, sequence, classification, observation, similarities and differences basic skills learning vocabulary. The methodological process that was applied for 25 students of first who grade participated in this study surveys and interview were used instruments to collect relevant information at unidad educativa Salinas Innova, during a period of 4 months. After implementing the proposal it was demonstrated that the application of gamification allowed increasing and reinforcing the vocabulary in the students of first grade.